ANALISA PERBANDINGAN OLI MESRAN DAN OLI PRIMA XP TERHADAP LAJU KEAUSAN PISTON HONDA GL 125 - Wijanarko, Heri; Sugihandoko; Lufti, Aryananta (PPM Sdirjianbang Akademi Militer, 2024)
Analysis in this case the Indonesian Army as a national defense tool requires a strong vehicle in all fields. Especially in the vehicle engine requires a type of lubricant that suits the characteristics of the engine. So that the performance of the vehicle engine can be maximized. In addition, with the right lubricant, maintenance costs, equipment replacement costs can be more efficient and fuel consumption is more efficient. The piston is a part that always moves continuously, so that lubrication can reduce friction and reduce wear on the piston. With proper lubrication, the piston will be more durable. In this analysis, we try to find the best type of lubricant that is resistant to wear from friction. So that the type of lubricant that is suitable is obtained according to the characteristics of the engine. And knowing how resistant to wear.